2017
DOI: 10.12988/imf.2017.7652
|View full text |Cite
|
Sign up to set email alerts
|

Permanents and determinants of tridiagonal matrices with (s,t)-Pell numbers

Abstract: In this study, we define a n × n tridiagonal matrix which have elements of (s, t)-Pell numbers and then investigate the determinantal properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The validity and reliability study of the scale in Turkish was performed and the Cronbach's α was found as 0.92 for the total scale. Cutoff scores for the anxiety subscale of 10 and 7 for the depression subscale have been accepted (Gulec et al, 2017).…”
Section: Patient Selection and Measuresmentioning
confidence: 99%
“…The validity and reliability study of the scale in Turkish was performed and the Cronbach's α was found as 0.92 for the total scale. Cutoff scores for the anxiety subscale of 10 and 7 for the depression subscale have been accepted (Gulec et al, 2017).…”
Section: Patient Selection and Measuresmentioning
confidence: 99%
“…The study shows that permanents of these matrices can be realized as Pell numbers, Fibonacci numbers, Lucas numbers and their sums. Similarly, in [2], Gulec studies an nn  tridiagonal matrix As a more intricated example, in [8], Minc considers a (0,1) nn  -matrix for which the , i j entry is 1 when…”
Section: Introductionmentioning
confidence: 99%